PENGEMBANGAN MEDIA PANCA (PAPAN BACA) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PADA PEMBELAJARAN BAHASA INDONESIA KELAS 1 SDN 10 KOTO BARU - Gunawan Ali; Ratnawati; Sonia Yulia Friska; Rokaiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the limited learning media and teachers in the process of teaching reading have not used media that is interesting for students at SDN 10 Koto Baru. Even though learning resources that use media are really needed to support teaching and learning activities so that learning objectives can be achieved. The aim of this research is to produce panca media (reading boards) to improve reading skill in class 1 indonesian language learning at SDN 10 Koto Baru that is valid, practical and effective for use in learning in class 1 elementary school. The research method used in this research in the Research and Development (R&D) method. In this research, the author only conducted research or simple research that focused on development. The model used is the ADDIE model which consists of 5 stages. Namely analysis, design, development, implementation, evaluation. The results of the five media validation (reading boards) were assessed by six expert validators, namely the material validation results were 0.88% with the valid category, the design validation results were 0.86% with the valid category. Based on the material and design results, the average score was 0.87% with the valid category. . The results of the validation of the teaching module were assessed by three expert validators, namely the validation results of content suitability were 0.87% in the valid category, the construction validation results were 0.85% in the valid category, the language competency validation results were 0.85% in the valid category. Based on the results of content feasibility, construction and language competency, the average score was 0.86% in the valid category. The results of the teacher response questionnaire data analysis, which was assessed by one teacher, obtained an average of 97.5% in the very practical category. Based on the results of the trial, student responses reached 93.62% in the very practical category. The results of the effectiveness of the learning assessment for class 1 students obtained an average of 87.5% in the very effective category.